The #TeachSDGs movement and global citizenship education: Soft openings, pluriversal possibilities (Journal of Applied Learning and Teaching, 2025)
This article examines how global citizenship education (GCE) is interpreted and understood by the #TeachSDGs movement, an online transnational, cross-level group of educators dedicated to disseminating the UN Global Goals (SDGs) through pedagogical resources. Drawing on Andreotti’s (2014) soft-to-critical GCE framework, the study deploys thematic and critical discourse analysis to assess the #TeachSDGs movement’s blogs, social media posts and lesson materials. The advocacy group’s online posts and classroom initiatives are found to be well-intentioned but risk reinforcing the colonially infused power dynamics and neoliberal logic responsible for the planet’s ecological crises and socioeconomic injustices. As such, seemingly benevolent narratives around technology, collaboration and empathy are interrogated for their uncritical and therefore, a soft approach to GCE. However, the study also reflects on the work of a minority of the movement’s members who confront colonial legacies, political hegemonies and power disparities, thereby engendering a more critical understanding of GCE. Lastly, the paper discusses the #TeachSDGs movement’s potential to imagine pluriversal possibilities, a postcolonial, post-development world consisting of many radically interconnected worlds (Escobar, 2020).